Standardized evaluation of hand‐off documentation of ICU boarders in the emergency department - Joshua Kolikof; Daniel Shaw; Bryan Stenson; Anne Grossestreuer; Leon Sanchez; David Chiu (Journal of the American College of Emergency Physicians Open)
Abstract Objective The boarding of ICU patients in the emergency department (ED) represents a considerable risk to patient safety. This study aims to describe the generation of a rubric to ensure the fidelity of vital, written hand‐off between ED teams. Methods We performed a mixed methods design to develop a scoring rubric to evaluate written hand‐off communication of medical ICU boarders between ED teams during the COVID‐19 pandemic. The primary outcome was the quality of the written hand‐off as agreed upon by the inter‐user agreement. Our secondary outcome included variability in written quality as a function of the number of separate and distinct ED teams at the point of the transition of care. Results There was a moderate inter‐user agreement with rubric scoring (κ = 0.70 [95% confidence interval, 0.66–0.75]). The overall trend noted that several key elements, including code status, performed interventions, and contingency planning, were infrequently documented. Conclusions We effectively created a quality assurance tool for ED ICU boarders that ensures relevant and vital information is relayed between ED teams. Our analysis demonstrated that all relevant information is only sometimes present in the hand‐off.